2003
DOI: 10.1542/peds.112.1.e17
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Vision Screening Frequency After an Office-Based Training Session for Primary Care Staff

Abstract: Direct, practical training in preliterate eye chart vision screening may increase the number of 3-year-old children screened and improve clinical support staff comfort with screening preschool children. A single training session is not sufficient in itself, however, to achieve the goal of universal preschool vision screening in the primary care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…[16] PHC service staffs after brief training were also utilized for eye and vision screening. [17] Comparison of outcome of different staff used for vision screening suggested that they were uniformly less efficient compared to the tests in eye clinics with adequate tools. [18] Validity of vision screening and eye examination by public health nurse was found less satisfactory in <41 month old children but was good in three to four-year-old children.…”
Section: Discussionmentioning
confidence: 99%
“…[16] PHC service staffs after brief training were also utilized for eye and vision screening. [17] Comparison of outcome of different staff used for vision screening suggested that they were uniformly less efficient compared to the tests in eye clinics with adequate tools. [18] Validity of vision screening and eye examination by public health nurse was found less satisfactory in <41 month old children but was good in three to four-year-old children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts to improve vision screening in the medical home at preschool age, using more traditional approaches, have reported similar challenges regarding recruitment, retention and patient outcomes, 47,48 with greater success possibly linked to higher baseline screening rates, provider choice from a menu of topics, and/or repeated, face-to-face visits. 6 However, no previous study has followed a randomized design or sought to assess and improve provider knowledge about vision.…”
Section: Discussionmentioning
confidence: 98%
“…A cross-sectional study of pediatricians in 1991 showed that vision screening was attempted on only 66% of children aged three to five years, with Hispanics less likely to be screened than other ethnic groups (Wasserman, Croft, & Brotherton, 1992). In a separate study of 29 pediatric and family physician practices, despite a training session, vision screening of four-year-olds remained low, with only 21 % of the practices reported to be screening nearly all of the children in that age group (Hered & Rothstein, 2003 Many preschool vision-screening guidelines and protocols exist. The National Eye Institute (NEI) funded the Vision in Preschooler (VIP) study, which examined 11 different vision-screening tests to determine their relative effectiveness in detecting important vision conditions, including amblyopia (Vision in Preschoolers Study Group, 2004).…”
Section: How Is Amblyopia Treated?mentioning
confidence: 99%